Eficiência de predação de espécies nativas sobre a espécie exótica Oreochromis niloticus em diferentes complexidades de habitat - Birck, Tiago (2015)
The practice of introducing species has brought great trouble to natural environments as a new species cause imbalance to the ecosystem and evolutionarily established his control has been one of the challenges for ecologists today. Thus, in mesocosms were experimentally analyzed the potential of juveniles of three species of piscivorous fish native (Salminus brasiliensis, Pseudoplatystoma corruscans and Brycon orbignyanus) in population control of Nile tilapia (Oreochromis niloticus) and the role of habitat complexity in this predator-prey interaction. The invasive species Oreochromis niloticus was offered in 2,000L tanks as prey for predators in 1:10 rate (predator:prey) with four levels of habitat complexity (0%, 50%, 100% and natural) without food supply. The number of exemplary preyed was evaluated with 6, 12, 24, 36, 48, 60, 72, 84, 96 and 108 hours after started of the experiment. Salminus brasiliensis showed the highest efficiency of predation, whereas the complexity of habitat did not influence the consumption of prey. In this sense, the sample results indicate that S. brasiliensis species is most effective to control of O. niloticus populations, thus constituting an alternative to implementations of management actions on aquatic environments of the Paraná River.